2009
DOI: 10.1002/elan.200804492
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Carbon Nanotube‐Hydroxyapatite Nanocomposite: Application to Anodic Stripping Voltammetric Determination of Cadmium

Abstract: A novel chemically modified electrode for stripping determination of cadmium is presented in this paper, based on carbon nanotube-hydroxyapatite (CNT-HAP) nanocomposite, which can be prepared by an easy and effective onestep sonication. The newly synthesized nanocomposite was characterized with FTIR, TEM, and electrochemical methods. Due to the combination of the strong absorption ability of HAP and excellent electroanalytical properties of CNTs, the GC/CNT-HAP electrode has been successfully used for determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…The spectrum for HA showed the well-resolved peaks at 565 cm −1 and 604 cm −1 which were attributed to v 4 P-O bending in phosphate group, the peaks at 960 cm −1 were assigned to v 2 OPO bending, and the peaks at 1064 cm −1 were attributed to the P-O stretching (Bhatnagar, 1971;Bhattarai et al, 2008). The split bands, mainly at 1038 cm −1 and 1091 cm −1 , were seemed to be coincided with the formation of a well-crystallized apatite (Yang et al, 2005;Pan et al, 2009). Moreover, a characteristic band corresponding to the hydroxyl group of HA was found at 3428 cm −1 .…”
Section: Characterization Of Cnts-ha Composite Filmmentioning
confidence: 94%
“…The spectrum for HA showed the well-resolved peaks at 565 cm −1 and 604 cm −1 which were attributed to v 4 P-O bending in phosphate group, the peaks at 960 cm −1 were assigned to v 2 OPO bending, and the peaks at 1064 cm −1 were attributed to the P-O stretching (Bhatnagar, 1971;Bhattarai et al, 2008). The split bands, mainly at 1038 cm −1 and 1091 cm −1 , were seemed to be coincided with the formation of a well-crystallized apatite (Yang et al, 2005;Pan et al, 2009). Moreover, a characteristic band corresponding to the hydroxyl group of HA was found at 3428 cm −1 .…”
Section: Characterization Of Cnts-ha Composite Filmmentioning
confidence: 94%
“…The toxicity of Pb(II) in humans mainly comes from its detrimental mimicking action of occupying the calcium binding sites on numerous calcium-dependent proteins cells, thus resulting in the corresponding impairment of physiological functions [1,2]. Due to unusual long half-life and accumulation in soft tissues like kidney and liver, Cd(II) is of toxicologically interest [3].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs exhibit an excellent electrical conductivity [5]. Although HA/CNT composites are a promising biomaterial for tissue engineering [6], recently some authors have reported their applications in electrochemistry [7,8]. Several articles have reported the synthesis of HA/CNT composites [6].…”
Section: Introductionmentioning
confidence: 98%